Impact of Surgical Ablation of Atrial Fibrillation on the Progression of Tricuspid Regurgitation and Right‐Sided Heart Remodeling After Mitral‐Valve Surgery: A Propensity‐Score Matching Analysis - Jiangang Wang; Jie Han; Yan Li; Qing Ye; Fei Meng; Tiange Luo; Baiyu Tian; Haibo Zhang; Yixin Jia; Wen Zeng; Chunlei Xu; Wei Han; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background This study assessed the role of surgical ablation for atrial fibrillation (AF) in decreasing tricuspid regurgitation (TR) and right‐sided heart remodeling in patients after mitral valve procedure. Methods and Results Between 1994 and 2014, 1568 consecutive patients with AF undergoing mitral valve procedure were identified. In 26.0% (n=408), surgical ablation of AF was used. Propensity‐score matching (PSM) was performed on the basis of 41 known perioperative risk variables. Survival, reoperation, stroke, and moderate‐to‐severe TR, as well as echocardiography indices in long‐term follow‐up, were compared in 406 matched patient pairs (ablated and nonablated groups). The nonablated group showed significantly higher risks of death (hazard ratio [HR], 1.644; 95% CI, 1.081–2.501; P=0.020), reoperation (HR, 2.644; 95% CI, 1.299–5.466; P=0.008), and moderate‐to‐severe TR (HR, 1.436; 95% CI, 1.059–1.948; P=0.020), associated with a significantly deteriorated cardiac function, progression of TR, and right‐sided heart remodeling after 5‐year follow‐up. In a subgroup comparison of ablated patients with sinus rhythm versus AF recurrence, a PSM analysis was performed at the 5‐year follow‐up. The recurrent group showed significantly higher risks of moderate‐to‐severe TR (HR, 2.427; 95% CI, 1.261–4.671; P=0.008). AF recurrence was associated with progressive TR and significant deterioration in right‐sided heart remodeling. Conclusions In a retrospective PSM analysis, mitral valve disease with AF was associated with TR progression as well as right‐sided heart remodeling, which are alleviated by surgical ablation.